Patterns of morphological and ecological similarities of small-eared shrews (Soricidae, Cryptotis) in tropical montane cloud forests from Mesoamerica. Issue 6 (18th August 2018) - Guevara, Lázaro; Sánchez-Cordero, Víctor
Abstract : It has been proposed that high morphological similarity between closely related species of small-eared shrews resulted from a recent divergence and intermittent population connectivity, presumably due to Pleistocene climatic fluctuations and associated changes in forest habitat distribution. Here we examined the morphological variation of two sister species of small-eared shrews inhabiting cloud forests from Mexico, Cryptotis obscurus and C. mexicanus . We then used ecological niche modelling to provide compelling evidence for current environmental barriers for population connectivity, and for detecting divergent ecological niches between candidate species. Our results indicated that the species boundaries in this clade should be subject to change. High morphological similarity suggested that populations of C. obscurus and C. mexicanus located west of the Isthmus of Tehuantepec, a major geographic barrier for montane species, are conspecific. Niche divergence between these two putative species was not supported indicating niche conservatism across the evolutionary history of these small-eared shrews. In addition, several barriers seem to play a main role for current lineage divergence between populations within this clade. The population located east of the Isthmus, previously referred to C. mexicanus, might prove to represent a new species based on morphological distinction and current geographic isolation. We have highlighted that estimating species' potential distributions provides insights to evaluating the effect of geographic barriers on lineage divergence and making stronger inferences when delimiting species.